2019
DOI: 10.5897/ajfs2018.1782
|View full text |Cite
|
Sign up to set email alerts
|

Status of commercial maize milling industry and flour fortification in Kenya

Abstract: Maize is the most widely consumed staple food by the Kenyan population. Its wide consumption and centralized processing make it an appropriate fortification vehicle to supply essential micronutrients to the population. The legislation was enacted in 2012 that makes it mandatory for all commercial maize mills in Kenya to fortify the maize flour with specified micronutrients as a public health effort to reduce the prevalence of micronutrient deficiencies. However, there is limited information on the current stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Recognizing the vital role played by smaller mills which cater to a significant portion of the population, there were subsequent pushes to help SMEs fortify their products, ensuring broader coverage. However, small millers found that the cost of fortification, spread over their relatively small volumes of maize flour, had a significant effect on profitability (Khamila et al, 2019). This example underscores the importance of regulatory incentives in helping tilt investments to meet broader nutrition goals, especially through larger enterprises.…”
Section: The Potential Pathways For Investment In Food Small and Medi...mentioning
confidence: 99%
“…Recognizing the vital role played by smaller mills which cater to a significant portion of the population, there were subsequent pushes to help SMEs fortify their products, ensuring broader coverage. However, small millers found that the cost of fortification, spread over their relatively small volumes of maize flour, had a significant effect on profitability (Khamila et al, 2019). This example underscores the importance of regulatory incentives in helping tilt investments to meet broader nutrition goals, especially through larger enterprises.…”
Section: The Potential Pathways For Investment In Food Small and Medi...mentioning
confidence: 99%
“…Hammer mills use simpler, smaller-scale technology, with many of the smallest hammer mills operating as toll mills (fee-for-service mills) that process grain brought to the mill by customers. There are several reasons why the law targets only packaged products: (1) It would be logistically and technically more demanding to monitor compliance in the country’s numerous hammer mills; (2) the incremental costs of fortification are higher for smaller scale millers, as there are economies of scale in fortification; and (3) size-appropriate fortification technologies (e.g., dosers) are difficult to access [ 31 33 ]. Many governments and development partners focus their food fortification initiatives on large firms, which are sometimes delineated as those with a processing capacity of more than 50 metric tons per day [ 6 , 31 , 32 , 34 ].…”
Section: An Application To Kenyamentioning
confidence: 99%
“…There are several reasons why the law targets only packaged products: (1) It would be logistically and technically more demanding to monitor compliance in the country’s numerous hammer mills; (2) the incremental costs of fortification are higher for smaller scale millers, as there are economies of scale in fortification; and (3) size-appropriate fortification technologies (e.g., dosers) are difficult to access [ 31 33 ]. Many governments and development partners focus their food fortification initiatives on large firms, which are sometimes delineated as those with a processing capacity of more than 50 metric tons per day [ 6 , 31 , 32 , 34 ]. Nevertheless, the Government of Kenya has expressed an intention to support fortification by small- and medium-scale industries [ 29 ].…”
Section: An Application To Kenyamentioning
confidence: 99%
“…Indeed, the characterization of the particles has a direct influence on the flowability as well as on the shaping (pelletization, extrusion), as documented by Šklubalová and Zatloukal (2013). The grinding itself is carried out using various mills, the most common being a hammer mill or a mill with rollers (Khamila et al, 2019).…”
Section: Introductionmentioning
confidence: 99%